Modern romance - Ansari, Aziz 1983-; Klinenberg, Eric (Allen Lane an imprint of Penguin Books, 2015)
People today have more romantic options than at any point in human history, and thanks to social media, smartphones and online dating, our abilities to connect with these options are staggering. Yet we also have to face new and absurd dilemmas, such as what to think when someone doesn't reply to your text but has time to post a photo of a pizza on Instagram. But this transformation of our romantic lives cannot be explained by technology alone. Whereas once most people would find a decent person who probably lived in their neighbourhood and marry by the age of 23, today we spend years of our lives on a quest to find our soulmate. While Ansari has long aimed his comedic insight at modern relationships, here he teamed up with award-winning sociologist Eric Klinenberg to research dating cultures from Tokyo to Buenos Aires to Paris, crunch the quantitative data and interview some of the world's leading social scientists. The result is an unforgettable tour of the romantic landscape.